Pemberdayaan Ekonomi Keluarga di Era Digital: Pendekatan Ekspansi Pasar melalui Pemasaran Online - Jam'an, Muhammad; Ummah, Hidayatul; Rohmawati, Siti Luthfi; Kartika, Ayu Dwi; Dewi, Rizka Amalia; Khusna, Aminatul; Pratama, Rizky Aditiya; Setiabudi, Agung; Nisa, Rofiatun (LP3M IAIFA Kediri, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy; however, many entrepreneurs still face obstacles in expanding their markets due to limited use of digital technology. A similar condition is found in Manyar Village, Sekaran Subdistrict, Lamongan Regency, where most MSME actors are housewives who rely on traditional marketing methods. This community service empowers family economies through digital marketing as a market expansion strategy. The objective is to improve digital literacy, branding capacity, and the ability to use e-commerce platforms among MSMEs so that they can expand their market access sustainably. The method employed was Participatory Action Research (PAR), which included problem identification, participatory planning, collective action, reflection, evaluation, and program sustainability monitoring. The program was carried out over one month, involving village officials, strategic partners (PT. Graha Rejeki Indonesia Kopi Giras and PT. Emer Inovasi Teknologi Cogan), and the active participation of local MSMEs. The results indicate that most participants successfully created marketplace accounts (Shopee and TikTok Shop), uploaded products with optimised descriptions and more professional photos, and began understanding the importance of branding and consistency in digital marketing. Moreover, the program increased the confidence of women entrepreneurs to market their products online while fostering the formation of a digital MSME community in Manyar Village. Therefore, this program enhanced digital skills, strengthened family economies, and established a village-based digital MSME ecosystem.